The Role of Work Ethics in Moderating the Effect of Islamic Business Ethics on the Income of Traders Around Religious Tourism - Ahmad Mifdlol Muthohar; Ari Setiawan; Jamaluddin Junaedi (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
This study aims to identify and analyze the factors that influence the income of traders with the work ethic as a moderating variable, a case study on religious tourism on the island of Java. Traders in the area of the Great Mosque of Demak were given questionnaires as part of the data collection process, the tomb of Sunan Kalijaga and the tomb of Raden Santri. The samples in this study were 40 respondents with a purposive sampling technique. The data were processed using the SPSS analysis tool version 16. The results showed that first, communication style, skills, length of business and business location, each partially, had no significant positive effect on trader income. Second, The income of traders is affected positively and significantly to some extent by business ethics.. Third, the work ethic variable is incapable to moderate the effect of communication style, skill, business length and business location partially on traders’ income. Fourth, the work ethic variable is able to moderate or strengthen the effect of Islamic business ethics on traders’ income.